Periodization of carbohydrate intake: Short-term effect on performance - Marquet, L.-A.; Hausswirth, C.; Molle, O.; Hawley, J. A.; Burke, L. M.; Tiollier, E.; Brisswalter, J. (Nutrients, 2016)
Background: "Sleep-low" consists of a sequential periodization of carbohydrate (CHO) availability—low glycogen recovery after "train high" glycogen-depleting interval training, followed by an overnight-fast and light intensity training ("train low") the following day. This strategy leads to an upregulation of several exercise-responsive signaling proteins, but the chronic effect on performance has received less attention. We investigated the effects of short-term exposure to this strategy on endurance performance. Methods: Following training familiarization, 11 trained cyclists were divided into two groups for a one-week intervention—one group implemented three cycles of periodized CHO intake to achieve the sleep-low strategy over six training sessions (SL, CHO intake: 6 g·kg-1·day-1), whereas the control group consumed an even distribution of CHO over the day (CON). Tests were a 2 h submaximal ride and a 20 km time trial. Results: SL improved their performance (mean: +3.2%; p < 0.05) compared to CON. The improvement was associated with a change in pacing strategy with higher power output during the second part of the test. No change in substrate utilization was observed after the training period for either group. Conclusion: Implementing the "sleep-low" strategy for one week improved performance by the same magnitude previously seen in a three-week intervention, without any significant changes in selected markers of metabolism.